2008
DOI: 10.1103/physrevb.77.172301
|View full text |Cite
|
Sign up to set email alerts
|

Homogenization of acoustic metamaterials of Helmholtz resonators in fluid

Abstract: By using a two-step homogenization approach, we derive analytical formulas of effective mass density e and effective bulk modulus B e for two-and three-dimensional acoustic metamaterials of Helmholtz resonators ͑HRs͒ in fluid. A negative B e is found at certain frequencies due to the monopolar resonance, leading to a low-frequency acoustic band gap. A unified picture is presented for metamaterials of HRs and three-component metamaterials of negative e . Our work supports recent observations in a one-dimensiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 26 publications
2
49
0
Order By: Relevance
“…Similar approximations have been used for a periodic array of circular scatterers [27]. The fluid layer is defined through the thickness h l = hF and density ρ l = ρ/F 2 with filling fraction F = Nd/(2πr o ) satisfying the following conditions:…”
Section: Low-frequency Approximationsmentioning
confidence: 99%
“…Similar approximations have been used for a periodic array of circular scatterers [27]. The fluid layer is defined through the thickness h l = hF and density ρ l = ρ/F 2 with filling fraction F = Nd/(2πr o ) satisfying the following conditions:…”
Section: Low-frequency Approximationsmentioning
confidence: 99%
“…An excellent review [64] points out that the majority of metamaterial homogenization studies published in the last decade failed to respect basic causality and passivity properties and in some cases also violated the second law of thermodynamics. Another broad technique for determining effective properties is through the Coherent Potential Approximation method [65] and its enhancements [66,67]. The metamaterial under study is embedded in a matrix, which has the properties of the effective media.…”
Section: Averaging Techniquesmentioning
confidence: 99%
“…In comparison with the numerous theoretical and experimental research results on electromagnetic metamaterials, research efforts on the acoustic metamaterials are relatively few and mainly concentrated on theoretical aspects [10,15,16,17,18,19,20]. Only, recently, Fang et al reported realization of negative modulus in a metamaterial consisting of Helmholtz resonators [11].…”
mentioning
confidence: 99%